The design of a prototype monitoring and control device for household electrical appliances based on the internet of things (IoT) using Pzem-004T sensor - Susanto, Eri Sasmita; Bulan, Santi; Dinola, Dinola (Jurnal Simantec, 2025)
The increasing demand for electrical energy poses challenges such as energy waste, which impacts household expenses and the environment. This study aims to design a prototype for monitoring and controlling electrical devices based on the Internet of Things (IoT) using the PZEM-004T sensor. The system is designed to provide real-time electricity consumption information through the Blynk application and allow users to remotely control electrical devices. This prototype utilizes an ESP32 microcontroller and a Solid State Relay (SSR) module for operation and monitoring. The development method used is prototyping, which includes requirement analysis, design, implementation, and testing. Testing was conducted in several households, and the results showed that the PZEM-004T sensor has a high accuracy level, with an average measurement error below 5%. The system provides detailed information on electricity consumption and enables energy savings through more efficient device control. The findings of this study are expected to serve as a practical solution for households to monitor and control electricity usage, support energy efficiency, and reduce electricity costs. Furthermore, this prototype can be further developed for larger-scale applications Keywords: device control, electricity monitoring, PZEM-004T sensor, Internet of Things (IoT)